2022
DOI: 10.3389/fmicb.2022.779505
|View full text |Cite
|
Sign up to set email alerts
|

Local Habitat Filtering Shapes Microbial Community Structure in Four Closely Spaced Lakes in the High Arctic

Abstract: Arctic lakes are experiencing increasingly shorter periods of ice cover due to accelerated warming at northern high latitudes. Given the control of ice cover thickness and duration over many limnological processes, these changes will have pervasive effects. However, due to their remote and extreme locations even first-order data on lake ecology is lacking for many ecosystems. The aim of this study was to characterize and compare the microbial communities of four closely spaced lakes in Stuckberry Valley (north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 100 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…2016) and the Canadian High Arctic (Marois et al . 2022). In addition, some of the most representative phyla in our lakes were reported to be abundant in marine and freshwater systems, including in the Antarctic, such as members of Proteobacteria and Bacteroidota (Rochera & Camacho 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2016) and the Canadian High Arctic (Marois et al . 2022). In addition, some of the most representative phyla in our lakes were reported to be abundant in marine and freshwater systems, including in the Antarctic, such as members of Proteobacteria and Bacteroidota (Rochera & Camacho 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Our analysis based on ASVs shows the dominance of phyla previously reported from high-latitude systems in studies employing NGS, such as in ice-free lakes from the Maritime Antarctic region (Byers Peninsula; Picazo et al 2019), ice-covered Laurentian Great Lakes (North America; Beall et al 2016) and the Canadian High Arctic (Marois et al 2022). In addition, some of the most representative phyla in our lakes were reported to be abundant in marine and freshwater systems, including in the Antarctic, such as members of Proteobacteria and Bacteroidota .…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence network patterns revealed that the complexity of microbial community in the Barkol Saline Lake habitat was: all>sediment>degraded area. This further indicates that lake degradation will first lead to the reduction of microbial species and diversity, and second, it will further reduce the stability of community structure, which is not conducive to the protection and maintenance of the saline lake habitat ( Marois et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The predicted prevalence of sulfur metabolism genotypes, particularly sulfate respiration genotypes, was much higher in sediment samples compared to degraded areas. However, climate change has aggravated the degradation of the saline lake in recent decades, and the salt composition of sediments has also gradually changed with outside conditions ( Marois et al, 2022 ). In Barkol Lake, the main salt was sulfate compounds such as sodium sulfate or gypsum; hence, sulfur-related microorganisms were long-established functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteriota accounted for approximately 20% of reads throughout the water column; cells of this phylum are typically small in size and are often abundant in oligotrophic freshwaters [ 61 ]. Planctomycetota (average of 19.8% of lake reads) has also been identified as an important feature of ice-covered lakes at the far northern coast of Ellesmere Island [ 62 ], and one of the main planctomycete families in Thores Lake, the Gemmataceae , is known to include psychrotolerant taxa [ 63 ]. The high relative abundance (13%) of Anaerolineales (Phylum Chloroflexi) is also unusual for most freshwater ecosystems and implies the importance of anoxygenic aerobic phototrophy in Thores Lake.…”
Section: Discussionmentioning
confidence: 99%